Proses Garapan Gerak Tari Sumbi Raksa - Mevia, Mevia (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research was motivated by students who were initially curious about the art of dance, how a dance movement work that has been seen so far is formed, such as in a show or on the internet, the idea of the sumbi raksa dance story is taken from folklore that has been passed down from generation. Before a dance is formed, a choreographer must first find dance concepts such as from searching for ideas, movements used, make-up, costumes, properties and there dancers used in the dance work. The method used in the sumbi raksa dance work is the exploratory method and the purpose of this study is to get an ideal of the sumbi raksa dance movement which is packaged in a folklore that has become a legend in west java which tells the story of a princess in west java named Dayang Sumbi, beautiful girl with a charming face. The figure of Dayang Sumbi is depicted as a woman who will always be young and have eternal beauty.